Could Hematologic Parameters Have a Predictive Role in Pediatric Hashimoto Thyroiditis? - Tarık Kırkgöz; Behzat Özkan (Galenos Publishing House, 2022)
Objective: Hashimoto thyroiditis (HT) is an autoimmune thyroid disease evolving as a result of lymphocyte infiltration and chronic inflammation. Although adult studies have shown that hematologic parameters, such as platelet-to-lymphocyte ratio (PLR) and neutrophil-to-lymphocyte ratio (NLR), and systemic immune-inflammation index (SII) can be used as biomarkers of HT, knowledge is limited concerning the pediatric age group. The aim of our study is to investigate the potential of hematologic biomarkers in predicting HT in children. Method: Children with HT (n=165) who were followed in the Pediatric Endocrinology Department of our hospital between July 2020 and July 2021, were enrolled in the present retrospective cross-sectional study. Hemogram values were compared with those of age-matched control group (n=122). Results: The average leukocyte (p>0.05), platelet (p>0.05), and absolute neutrophil (p>0.05) counts, NLR (p>0.05) and SII (p>0.05) in the children with HT were not statistically different from those of the control group. Although PLR values were significantly higher in the HT group than the control group (p<0.05), in receiver operating characteristic curve analysis, PLR values had low specificity and sensitivity, in predicting HT. Conclusion: Our study has shown that NLR and SII are not useful indicators in predicting HT in children. Although there is a statistically significant difference in PLR values, we think that PLR is not a useful marker due to its low specificity and sensitivity.